Plywood from Indian Timbers: Alnus nitida (Alder) - Shukla, K. S.; Shukla, L. N.; Chandra, Ramesh (Indian Forester, 1988)
Suitability of Alnus nitida (Alder) was studied for making various grades of plywood and blockboards with commercial adbesives viz., U-F and P-F. Alder is suitable for making plywood for general purpose, preservative treated plywood, fire retardant treated plywood, plywood for concrete shuttering work and for blockboard. It is also easy to treat with water soluble preservatives and fire retardant chemicals, which do not affect the glue bond to any great extent. Alnus nitida therefore, could be included in the list of species recommended for the above purposes in the various Indian Standard Specifications.